The Influence of Corporate Governance on Environmental Disclosure of Listed Non-Financial Firms in Nigeria - Odoemelam, Ndubuisi; Okafor, Regina G. (Indonesian Journal of Sustainability Accounting and Management, 2018)
The study investigates the influence of corporate governance on environmental disclosure of nonfinancial firms listed in Nigeria Stock Exchange (NSE), anchoring on “Trinity theory” (agency, stakeholder and legitimacy theories). 86 firm-year observations across 86 companies listed in Nigeria Stock Exchange (NSE) using content analysis, cross-sectional data, OLS regression techniques were used to analyze the influence of board characteristics on the extent of overall environmental disclosure (OED). The results show that board independence, board meeting, and the environmental committee were statistically significant while audit committee independence and board size were insignificant. Among the three company attributes used to mitigate spurious result only firm size significantly influence the quantity of overall environmental disclosure of the sample companies. Auditor type “big 4” (Ernest Young, Deloitte, KPMG, and PwC) and industry membership show insignificant relation to environmental disclosure. The findings indicate that the level of environmental disclosure of nonfinancial companies in Nigeria is quite insufficient at an average of 10.5 percent. It is not surprising that environmentally sensitive industry and auditor type had no significant influence on the extent of environmental disclosure. This buttress the point that the environment the companies operate is institutionally and legally weak. Hence it calls for improvement on environmental law and implementation as well as harmonized environmental reporting infrastructure and standard to aid comparison.